Spatial correlation study on the impact of green financial development on industrial structure upgrading - Nian, Wei; Dong, Xiaohong (Frontiers in Environmental Science, 2022)
Concern has been raised about how to effectively encourage industrial structure upgrading using green finance as a tool in the framework of sustainable development. This paper is based on the data from 2009-to 2018, the social network had been constructed using the gravitational model. Also, the spatial correlation of green finance development on industrial structure upgrading was studied through using the social network analysis method, as well as the detection analysis of the impact factor of green finance on industrial structure upgrading was conducted by using the geographic detector. The empirical results showed that: green finance and industrial optimization had entered a differentiated development stage in each province; green finance development would have an effect on upgrading industrial structure; and the overall network had established and maintained a benign development trend. This paper suggests that the government must improve the green finance management system as soon as possible, effectively use green finance to promote industrial optimization and introduce policies as per the characteristics of each province in order to promote the coordinated development of green finance in each province.